URGENSI PERUBAHAN UNDANG-UNDANG NOMOR 32 TAHUN 2002 TENTANG PENYIARAN - Denico Doly (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2013)
Broadcasting Act is the legal basis for broadcasters and regulators in the field of broadcasting in carrying out their duties and responsibilities. Setting the Broadcasting Act are no longer able to reach all aspects of broadcasting activities in Indonesia. The setting in the Broadcasting Act is still considered weak by many things. Weakness in the Broadcasting Act related to the weakening of the KPI effort, Networked Broadcast System that do not materialize, the weak institutional status of LPP, weak regulation of LPK, and not realize the implementation of restritions on the ownership of LPS. Therefore, the need for fundamental changes to the Law No. 32 Year 2002 on Broadcasting associated with efforts to strengthen KPI. Reaffirmation network broadcast system, institutional strengthening LPP, reinforcement pf LPK, and assertion of ownership restriction LPS.ABSTRAKUU Penyiaran merupakan landasan hukum bagi lembaga penyiaran maupun regulator dibidang penyiaran dalam melaksanakan tugas dan tanggung jawabnya. Pengaturan dalam UU Penyiaran tidak lagi dapat menjangkau seluruh aspek kegiatan penyiaran di Indonesia. Pengaturan dalam UU Penyiaran masih dianggap lemah oleh berbagai kalangan. Kelemahan dalam UU Penyiaran terkait dengan upaya pelemahan KPI, Sistem Siaran Berjaringan yang tidak terlaksana, lemahnya status kelembagaan LPP, lemahnya pengaturan tentang LPK, dan belum terlaksananya pembatasan kepemilikan LPS. Oleh karena itu, perlu adanya perubahan mendasar bagi Undang-Undang Nomor 32 Tahun 2002 tentang Penyiaran terkait dengan upaya penguatan KPI, penegasan kembali sistem siaran jaringan, penguaran kelembagaan LPS, penguatan LPK dan penegasan pembatasan kepemilikan LPS.